Bathing in Architecture; An exploration of the public spa as an architectural typology supporting everyday well-being - Matsuhashi, Linda; Vennberg, Hanna (My University, 2026)
The experience of bathing is deeply intertwined with the expe rience of architecture; it is a meeting between body, space, and material. Once a collective ritual and later a private necessity, the history of bathing reflects shifts in how people have understood health, the body, and society itself. In contemporary Sweden, public swimming halls are a place for exercise and are largely available. Meanwhile, spas devoted to mental well-being have become exclusive destinations, detached from the everyday. This thesis explores the public spa as an architectural typology supporting everyday well-being. The design proposal is located by the river in Klippan, Gothenburg. Today, the site functions as a parking lot; but there are plans by the municipality to transform the area into a residential neighbourhood in the near future. The shared bath is integrated within the development plan to further enhance the site’s potential. Through the study of light, materiality, and spatial configuration, the project investigates how the built environment can affect the atmosphere in a public spa. Grounded in literature and informed by built reference projects, the research applies design-based methods including model making and sketching. The result is a public spa focusing on the experiences of the visitor. The journey from the outside to the inside and around the bath is composed of a series of spatial and light sequences, creating a rhythm of movement and stillness. A place where great care has been put into balancing the sense of seriousness with welcoming gestures - where the bathing ritual becomes a part of the everyday.
Keywords: thermal bath, natural stone, waterfront, bathing ritual